Concurrent anti-glomerular basement membrane disease and membranous nephropathy: a case report - Li, Lin-Lin; Niu, Pei-Yuan; Li, Na; Zhang, Xiao-Ling; Cao, Hui-Xia (Frontiers in Medicine, 2025)
Anti-glomerular basement membrane (GBM) disease is a rapidly progressive glomerulonephritis which, in rare instances, occurs concurrently with membranous nephropathy (MN). We report a case of this patient presented with proteinuria and hematuria, the predominant pathology was crescentic and necrotizing glomerulonephritis with linear staining for immunoglobulin G (IgG) along the glomerular basement membrane (GBM) associated with epi-membranous electron dense immune deposits. The patient tested had significant titers of anti-GBM antibodies (196.27 RU/ml; reference range:0–20 RU/ml), and renal biopsy demonstrated diffuse strongly positive granular staining for phospholipase a2 receptor (PLA2R) along the GBM. The patient received therapy including prednisone, plasmapheresis and CD20 antibodies, which resulted in the clearance of anti-GBM antibodies and eventual recovery of renal function, as evidenced by the return of serum creatinine to normal levels. Earlier diagnosis and timely effective treatments could improve patients' prognosis.